Poverty measurement in Malaysian zakat institutions: a multidimensional perspective / Arifin Md Salleh, Mohd Fauzi Mohd Harun and Mohamed Saladin Abdul Rasool - Md Salleh, Arifin; Mohd Harun, Mohd Fauzi; Abdul Rasool, Mohamed Saladin (Research Management Institute (RMI), 2012)
Poverty is a situation exemplified by insufficent material resources. For many years this situation is explained through the perspective of material shortcomings especially from the perspective of income. However, poverty is no longer defined objectively but it exists in a multidimensional nature (Narayanan et al. 2000 ; Laderchi, 2000). It is not solely looked from the perspective of material resources but depends on how it is perceived and how it is measured, meaning it depends on who defines it (Mohd Fauzi Harun, 2007). The most common approach used by economists to explain poverty is the monetary approach (Laderchi, 2000; Asselin and Dauphin 2001). Specifically, poverty means a person unable to obtain a certain level of income to attain economic wellbeing or in an aggregate term explained as lacking of economic welfare (Ravallion, 1998). This approach is based on the utility theory which explains an invidual would attain satisfaction from consumption of goods and services (Asselin and Dauphin, 2001). Individually, the concept of wellbeing is widely used to explain the level of satisfaction, while in the aggregate context, the concept of economic welfare is used to explain the wellbeing of the society…